Investigations of seismic response to an irregular-section subway station structure located in a soft clay site. (15th August 2020) - Tang, Baizan; Li, Xiaojun; Chen, Su; Zhuang, Haiyang; Chen, Hua-Peng
Highlights: Seismic response and damage mechanism of irregular-section underground structure in a soft site were researched. Some advanced testing method were used to measure the deformation of the site and underground structure. Soil Surface settlement is significantly correlated with Arias intensity. Abstract: In this study, shaking table tests were performed to investigate the dynamic interaction of a silty-clay soil with an irregular-section subway station. During the tests, a shape acceleration array (SAA) was used to measure the lateral deformation of the model soil, and a non-contact dynamic displacement testing method was applied to visualize and digitalize the seismic damage process of the station structure. Typical test results, including the dynamic earth pressure, seismic settlement, deformation, and acceleration of different levels of the structure, were interpreted. The results indicated that the movement of the subway station was more controlled by the surrounding silty-clay soil in terms of phase and amplitude. SAA can effectively measure the soil deformation, and the relationship between the relative lateral displacement and soil depth can be well fitted in a cosine function, especially when subjected to strong earthquakes. Seismic settlement is significantly linked to Arias intensity, and the subway station experienced significant uneven settlement, resulting in soil-structure separation in the vertical direction. The multi-story irregular-section subway station deforms in a shear mode. The maximum inter-story drift ratio was approximately 1/171. The components in the lower layers of the shallow-buried subway station structure, particularly in the central columns, underwent cumulative damage. Hence, more robust forms of structural members and the ductility of central columns should be carefully considered in the seismic design of subway station structures.